The impact of new population policies on women's reproductive health pattern in Ardabil, Iran: a comparative cross-sectional study - Nejhaddadgar, Nazila; Mardi, Afrouz; Zare, Maryam (Frontiers in Reproductive Health, 2025)
BackgroundFamily planning helps couples make voluntary, informed, and responsible decisions about having children based on their economic, physical, and psychological capabilities. New population policies have banned family planning services in Iran. This study sought to investigate the impact of these policies on women's reproductive health pattern in Ardabil, Iran.MethodsA comparative cross-sectional study was conducted on 800 eligible women (in two groups of 400, pre/post new policies) attending health centers in Ardabil. Health centers were chosen using a stratified cluster method, and the eligible women were selected through convenience sampling. A researcher-designed questionnaire was used to collect data on demographic characteristics, reproductive health history, and contraceptive use in the past six months. Data were analyzed using SPSS version 24, with Z and Chi2 statistical tests.ResultsThe majority of women were aged 15–24 (45.25% and 53%), had education levels below a diploma (52.5% and 47%), and were housewives (88.5% and 84.75%). Prior to the policy change, 67.25% of women used modern contraception methods, compared to 31% after. Rates of unwanted pregnancies increased from 28.5% to 49.25%, and the incidence of one abortion rose from 14.25% to 21.75%. These differences were statistically significant (p < 0.05).ConclusionThe ban on family planning services has led to a shift towards traditional contraception methods, an increase in unwanted pregnancies, and unsafe abortions. This highlights the need for health policymakers to implement appropriate interventions.